Design and manufacturing tolerances optimisation with quality loss functions. (11th August 2010) - Muthu, P.; Dhanalakshmi, V.; Sankaranarayanasamy, K.
The competition in the current world market has forced the manufacturers to produce products with low cost and high quality. Production of high quality products at low cost requires the concurrent optimisation of design and manufacturing tolerances along with quality loss. Tolerance allocation is a design tool for minimising over-all cost of manufacturing, while meeting target levels for quality. Since, in traditional method, the allocation of tolerances is based on designer's own experience, it may significantly affect a product's quality and the resulting manufacturing costs. Hence, in this work, the tolerance allocation problem is formulated as a non-linear integer model by considering both the design and manufacturing tolerances so as to minimise the manufacturing cost and quality loss. Genetic algorithm is employed to solve the model and an example is presented to illustrate the methodology. Results are compared with conventional techniques and the performances are analysed.